Isolation and characterization of bacteria found on surface of automated teller machine (ATM) / Norazlia Aida Md Azmi - Md Azmi, Norazlia Aida (Faculty of Applied Sciences, 2017)
The ATM machine due to vast contact by multiple users can be contaminated by bacteria whether pathogenic or non-pathogenic. Constant handling from multiple users and the heat generated by the machine itself create a favorable breeding area for all sorts of bacteria. The emergence of infectious diseases causes an increase threat to human health. This study aims to isolate bacteria from ATM machines and to identify and characterize the morphology of bacteria that colonizes the ATM machine. Colony morphology is performed to examine the form, texture, appearance, size, shape and pigmentation of bacteria and catalase test, oxidase test and Triple Sugar Iron test used to identify the bacteria. This study revealed that the ATMs are all positive for bacterial strains. Pathogenic bacteria found are from the Klebsiella sp., Pseudomonas sp., and Enterobacter sp. it is advisable to disinfect the machine using alcohol wipes for example before and after using the machine as to limit the transmission and accumulation of bacterial with ATM.